Discussing Out‐of‐Pocket Costs With Patients: Shared Decision Making for Sacubitril‐Valsartan in Heart Failure - Smith, Graham H.; Shore, Supriya; Allen, Larry A.; Markham, David W.; Mitchell, Andrea R.; Moore, Miranda; Morris, Alanna A.; Speight, Candace D.; Dickert, Neal W. (Journal of the American Heart Association, 2019)
Background "Financial toxicity" is a concern for patients, but little is known about how patients consider out-of-pocket cost in decisions. Sacubitril-valsartan provides a contemporary scenario to understand financial toxicity. It is guideline recommended for heart failure with reduced ejection fraction, yet out-of-pocket costs can be considerable. Methods and Results Structured interviews were conducted with 49 patients with heart failure with reduced ejection fraction at heart failure clinics and inpatient services. Patient opinions of the drug and its value were solicited after description of benefits using graphical displays. Descriptive quantitative analysis of closed-ended responses was conducted, and qualitative descriptive analysis of text data was performed. Of participants, 92% (45/49) said that they would definitely or probably switch to sacubitril-valsartan if their physician recommended it and out-of-pocket cost was $5 more per month than their current medication. Only 43% (21/49) would do so if out-of-pocket cost was $100 more per month ( P<0.001). At least 40% across all income categories would be unlikely to take sacubitril-valsartan at $100 more per month. Participants exhibited heterogeneous approaches to cost in decision making and varied on their use and interpretation of probabilistic information. Few (20%) participants stated physicians had initiated a conversation about cost in the past year. Conclusions Out-of-pocket cost variation reflective of contemporary cost sharing substantially influenced stated willingness to take sacubitril-valsartan, a guideline-recommended therapy with mortality benefit. These findings suggest a need for cost transparency to promote shared decision making. They also demonstrate the complexity of cost discussion and need to study how to incorporate out-of-pocket cost into clinical decisions.